In Vitro Effect of Aqueous Extract of Moringa Oliefera Plant on Acanthamoeba Spp - Abdulbaki , Zainab Alaa; Alsamir , Shaimaa A.; Almansour, Nasir Abd Ali (Jour Med Resh and Health Sci, 2023)
Acanthamoeba spp. is a parasite that can significantly destroy vision. It enters eyes through polluted water or contact lenses , and starts to kill eyes epithelial cells. The aim of this paper is to study the lethal effect of Moringa oliefera aqueous plant extract on Acanthamoeba spp. In vitro.Samples of Moringa oliefera plants were acquired from nurseries in Basra province. Following the creation of plant extracts, (GC-MS) was used to identify the active components. Results revealed the presence of bioactive components like : tannins, glycosides, alkaloids, flavones and phenols in the used extracts . Corneal samples were collected from patients infected with AK in Basrah’s teaching hospital. The isolated protozoan has been morphologically classified to the genus level depending on cyst morphology declared by Page F.C. (1967), and it has been given the genus A. Castellani. Plant extracts from M. oliefera have been examined in vitro for their capacity to destroy Acanthamoeba cells. Acanthamoeba trophozoites were used in a number of (6 x 104 )cells per ml. A three separated repeatition experiments’ were done to evaluate of M. oliefera aqueous plant extract effect on this protozoan.